2014
DOI: 10.3233/npm-1474113
|View full text |Cite
|
Sign up to set email alerts
|

Positive distending pressure produced by heated, humidified high flow nasal cannula as compared to nasal continuous positive airway pressure in premature infants

Abstract: OBJECTIVE: our objective is to assess the positive distending pressure generated by high flow nasal cannula and nasal continuous positive airway pressure by measuring the end esophageal pressure in premature infants. STUDY DESIGN: This is a pilot, non-randomized, open label, uncontrolled, crossover assignment study that included neonates born with a birth weight of 1750 grams or less and receiving nCPAP ventilatory support for 24 hrs or more and requiring FiO2 21-50% on nCPAP. Each infant was started on nCPAP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…HHHFNC generated EDP at flow rate up to 2.5 L/min in infants weighing < 2000 g. Saslow et al 29 compared NCPAP at 6 cmH 2 O and HHHFNC at 4 L/min, 5 L/min, and 6 L/min. The EDPs were similar in both systems but < 2 cmH 2 O. Alaiyan et al 39 set the flow rate of HHHFNC at 4 L/min, 6 L/min, and 8 L/min and NCPAP pressure was set at 4 cmH 2 O, 6 cmH 2 O, and 8 cmH 2 O. Their study demonstrated that HHHFNC was able to deliver almost equal EDP to NCPAP: 4.5e6.7 cmH 2 O and 3.6e6.3 cmH 2 O, respectively (Table 1).…”
Section: Nasopharyngeal Pressure and Edpmentioning
confidence: 77%
“…HHHFNC generated EDP at flow rate up to 2.5 L/min in infants weighing < 2000 g. Saslow et al 29 compared NCPAP at 6 cmH 2 O and HHHFNC at 4 L/min, 5 L/min, and 6 L/min. The EDPs were similar in both systems but < 2 cmH 2 O. Alaiyan et al 39 set the flow rate of HHHFNC at 4 L/min, 6 L/min, and 8 L/min and NCPAP pressure was set at 4 cmH 2 O, 6 cmH 2 O, and 8 cmH 2 O. Their study demonstrated that HHHFNC was able to deliver almost equal EDP to NCPAP: 4.5e6.7 cmH 2 O and 3.6e6.3 cmH 2 O, respectively (Table 1).…”
Section: Nasopharyngeal Pressure and Edpmentioning
confidence: 77%
“…However, use of HHFNC in children continues to increase both within and outside of the ICU and has been shown to deliver variable amounts of positive airway pressure. [15][16][17][18][19] As a result, some authors combine both NIPPV and HHFNC when studying noninvasive respiratory support. 20,21 The overlap in definitions, physiologic effects, and patient populations who require escalated respiratory support in the form of HHFNC and NIPPV makes discriminating between the modalities for research purposes increasingly difficult.…”
Section: Discussionmentioning
confidence: 99%
“…All these approaches improve oxygenation by reducing ventilation-perfusion mismatch and work of breathing, and are effective in treating AOP. [31][32][33][34][35] Recently, a novel flowsynchronized NIPPV method has been suggested as more effective than conventional NIPPV or CPAP for premature infants with AOP. 36 The different devices/methods have specific advantages and disadvantages that are beyond the scope of this review.…”
Section: Treatment Of Apnea Of Prematuritymentioning
confidence: 99%